Employee perspectives on sex trafficking in Swedish chain hotels. Issue 1 (2nd January 2023) - Rossi, Eleonora; Thulemark, Maria; Duncan, Tara
ABSTRACT: This paper investigates chain hotel employees in Sweden and their ability to work against sex trafficking. Using ten semi-structured interviews, the research asks questions about employee's relationships with external stakeholders (the police, booking channels, non-profit organizations, and competitors) and macroenvironmental factors (political and legal factors, economic, socio-cultural and health). The findings highlight that lack of communication, cooperation and autonomy hinder chain hotel employee's ability to recognize and prevent sex trafficking. The paper concludes by emphasizing the need for better interdisciplinary engagement to help eliminate sex trafficking within the tourism and hospitality industries and reiterates the call for actionable outcomes that empower chain hotel employees to work with external stakeholders to find viable solutions to help stop sex trafficking.